Impact of Magnetic Field Strengthening on Combustion Performance of Low-Octane Fuel in Two-Stroke Engine - Wibowo, N. A.; Utami, S. M.; Riyanto, C. A.; Setiawan, A. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2020)
The impacts of strengthening magnetic field exposure on combustion performance of low-octane fuel have been examined experimentally. The combustion test was carried out using a 2-stroke 49 cc engine where the fuel was magnetized using a low magnetic field (<2 kG). Moreover, the molecular behavior of magnetized fuel was also characterized through spectrum tests using NIR and UV-Vis spectrophotometers. The result of this study indicates an exponential decrease of magnetized fuel consumption against the strengthening of magnetic field exposure. This exponential decrease of consumption can be related to the Arrhenius principle. In addition, the decrease of oxygen in the exhaust gas along with the strengthening of the magnetic field also confirms the increase of combustion reactions. Meanwhile, the increase of magnetized fuel absorption against ultraviolet and near-infrared lights along with the increase of the magnetic field intensity indicates a bond weakening, accompanied by the increase of molecular vibrational energy.